2023
DOI: 10.1063/5.0152863
|View full text |Cite
|
Sign up to set email alerts
|

Thermal switch based on ferroelasticity VA-N binary compounds

Abstract: Ferroelastic materials possess two or more equally stable orientation variants and can be effectively modulated via external fields, including stress and electronic field. In this paper, taking the VA-N ferroelastic materials as examples, we propose a thermal switch device based on their ferroelastic characteristics. The results show that the VA-N binary compound exhibits excellent ferroelasticity, high reversible elastic strain (5.5%–54.1%), and suitable switching energy barriers (0.012–0.386 eV/atom) in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…43 With the development of the big data and the articial intelligence technology, ML approaches have been extensively employed in materials genome initiatives and materials informatics. [44][45][46][47] For example, several 2D crystals that haven't been previously classied as favorable TE materials were iden-tied through high-throughput screening function, 48 thermoelectric performance for a series of layered IV-V-VI semiconductors was predicted by ML, 49 and accurate prediction of k L for metastable silicon crystals was accelerated by ML potential. 50 The data-driven ML methods provide new opportunities to accelerate the discovery of promising A 2 BX 2 thermoelectric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…43 With the development of the big data and the articial intelligence technology, ML approaches have been extensively employed in materials genome initiatives and materials informatics. [44][45][46][47] For example, several 2D crystals that haven't been previously classied as favorable TE materials were iden-tied through high-throughput screening function, 48 thermoelectric performance for a series of layered IV-V-VI semiconductors was predicted by ML, 49 and accurate prediction of k L for metastable silicon crystals was accelerated by ML potential. 50 The data-driven ML methods provide new opportunities to accelerate the discovery of promising A 2 BX 2 thermoelectric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelasticity is similar to ferromagnetism or ferroelectricity characterized by strain–stress hysteresis loop. Ferroelasticity refers to the nonlinear shape response due to mechanical forces. Because of this, ferroelastic materials can be widely used in mechanical switches, signal conversion, memory materials, and other fields. Since Salje et al first observed the elastic hysteresis loop on Pb 3 (PO 4 ) 2 in 1976, , a large number of pure inorganic ferroelastic materials (such as Li 2 SrNb 2 O 7 , KFe­(MoO 4 ) 2 , and BiVO 4 ) have gradually come into view in recent years. However, the main drawback of these inorganic ferroelastic materials lies in their manufacturing difficulties, high cost, and large energy consumption .…”
Section: Introductionmentioning
confidence: 99%